PERUSAKAN HUTAN DI KABUPATEN TAKALAR PERSPEKTIF SIYASAH SYAR’IYYAH - Pausi, Dedy; Wijaya, Abdi (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2020)
This study aims to describe how the preservation of forests in Takalar District, how the form of forest destruction in Takalar District, and How sanctions are given by the government for the perpetrators of forest destruction in Takalar District. This research is a kind of descriptive qualitative field research (field research). The results of this study indicate that: 1). Forest preservation in Kab. Takalar is a form to prevent the occurrence of continuous forest destruction, and prevent the occurrence of deforested forests caused by humans, whether intentional (greed) or unintentionally in the preservation of this forest, there are several forms, one of them is the forestry or unity forest management conducts reforestation, which is replanting trees into forest environments that are no longer suitable for occupancy. 2). Form of forest destruction in Kab. Takalar is a familiar human behavior carried out in the life of the community even in the form of forest destruction made as a source of community income, these hereditary habits that cannot be changed by the forestry or forest management units at this time in Kab. Takalar 3). Commitment to the perpetrators of forest destruction in Kab. Takalar was present because of an act of violation which was caused by unscrupulous persons imposing penalties/sanctions on the destruction of the forest, such as fines and imprisonment.